(untitled) (Web of Teachers: Inderscience Research, 2025)
The social and cultural impact of globalization on family values is scientifically analyzed in this article. It highlights the correlation between traditional family values and modern trends. During the research, the spiritual factors that ensure the stability of Uzbek families were identified. The pros and cons of globalization are also analyzed. The article substantiates the role of the family as a social institution and its role in the stability of society. The author emphasizes the need to preserve family values, while adapting them to modern life. As a result, the harmony of national and global values is recognized as an important factor of family strength.